(untitled) (diségno, 2018)
Knowing, digitalizing, sharing represent the key concepts of this millennium. The construction and Real Estate sectors have the opportunity to take up this challenge by becoming promoters of intelligent data management that characterize buildings. The Building Information Modelling (BIM) methodology, strengthened by the unstoppable technological progress, lays the groundwork for re-designing a structured knowledge system of the building heritage. This triggers a new concept of Cadastre of the Future, dynamic and updated, which interrogates the Big Data of the buildings according to a multidisciplinary and interoperable approach. The perspective is ambitious, but it is essential to define the correct methodological approach to govern the digitization of built heritage. The setting up of the first experimentations is carried out on the City of Turin. Pursuing the vision of augmented digital city, an interactive map has been created, exploiting new technologies, such as Augmented and Virtual Reality, to enable the dissemination of information to different types of users.